ESSDERC 2008 - 38th European Solid-State Device Research Conference 2008
DOI: 10.1109/essderc.2008.4681704
|View full text |Cite
|
Sign up to set email alerts
|

Atomically flat gate insulator/silicon (100) interface formation introducing high mobility, ultra-low noise, and small characteristics variation CMOSFET

Abstract: Atomically flat silicon surface constructed with atomic terraces and steps is realized by pure argon ambience annealing at 1200 o C on (100) crystal orientation large diameter wafers with precisely controlled tilt angle. Only the radical reaction based insulator formation technology such as oxidation utilizing oxygen radicals carried out at low temperature (400 o C) can preserve the atomically flatness at the gate insulator film/silicon interface. CMOSFET having the atomically flat interface exhibit extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…However, almost no increase was observed for E eff larger than 0.8 MV/cm. 8) The impact of interface flatness to the electron mobility has been experimentally confirmed at high E eff region when the roughness level is relatively large such as R a ranging from 0.2 to 1.5 nm. 7,29,30) The experimental results obtained in this work shows that the electron mobility is less sensitive to the flatness under the atomic scale flatness level at high E eff region and actually more sensitive at relatively low E eff region.…”
Section: Carrier Mobility Characteristicsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, almost no increase was observed for E eff larger than 0.8 MV/cm. 8) The impact of interface flatness to the electron mobility has been experimentally confirmed at high E eff region when the roughness level is relatively large such as R a ranging from 0.2 to 1.5 nm. 7,29,30) The experimental results obtained in this work shows that the electron mobility is less sensitive to the flatness under the atomic scale flatness level at high E eff region and actually more sensitive at relatively low E eff region.…”
Section: Carrier Mobility Characteristicsmentioning
confidence: 90%
“…For hole mobility, an unique temperature point was found at around 180 K where the E eff dependency of mobility increase crosses over. 8) It should be noted that at the high E eff region, the improvement of the hole mobility is larger than that for electron mobility. This result indicates that the hole mobility is more sensitive to the flatness than that of electron at the atomic scale flatness level.…”
Section: Carrier Mobility Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…The interface roughness degrades not only electron mobility [66][67][68][69][70][71] and gate dielectric reliability [72][73][74], but also noise generation [71,75,76]. An atomically flat interface [77][78][79][80][81][82][83][84] is effective for reducing low-frequency noise [79,[83][84][85][86][87].…”
Section: Mosfets With Atomically Flat Gate Insulator/si Interfacementioning
confidence: 99%
“…[6][7][8][9] Also, an introduction of (110) orientation surface as well as, the improvement of flatness between gate insulator film/silicon interface have been studied to increase the relaxation time constant of lattice phonon scattering for holes and interface roughness scattering for both electrons and holes, respectively. [10][11][12][13] It is well known that the heavy hole effective mass has a direction dependency. 14) Sayama et al reported on the improved current drivability of p-channel MOSFET (pMOS) on (100) surface along the [001] channel direction instead of the conventional [011] channel direction.…”
Section: Introductionmentioning
confidence: 99%